PEMBERDAYAAN EKONOMI MASYARAKAT BERBASIS KEARIFAN LOKAL (STUDI KASUS PETANI SALAK TAPANULI SELATAN) - Harahap, Muhammad Ikhsan; Harahap, Rahmat Daim (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2023)
Sihopur South Tapanuli Village has the potential to produce snakefruit. However, many snake fruit are not used because they are not worth selling. The business group of salak farmers utilizes unsold fruit by creating salak cake, but in terms of taste and packaging it is not yet suitable for marketing. To increase the income of salak farmer business groups, diversification of processed salak products is needed. Furthermore, to increase sales, digital marketing is needed. To support salak farmers, community service was held using the Community Based Research (CBR) method. Implementation of community service begins with initial observations, then carrying out focus group discussions (FGD) and then carrying out diversification training and digital marketing training. As a result of training on salak diversification, the Sihopur village salak farmer business group has created salak bolu with a more attractive appearance, then the salak farmer group has also created salak sukade and salak biscuits. As a result of digital marketing training, salak farmers in Sihopur village have been able to use a Google business account to market their processed salak products. Furthermore, the salak farmer business group has also succeeded in obtaining a business registration number (NIB) as a legal business